A Study of Autonomous Navigation of a Robot Model based on SLAM, ROS, and Kinect - Ganiev, Asilbek; Hee Lee, Kang (International Journal of Engineering and Technology, 2018)
In this paper, we used a robot operating system (ROS) that is designed to work with mobile robots. ROS provides us with simultaneous localization and mapping of the environment, and here it is used to autonomously navigate a mobile robot simulator between specified points. Also, when the mobile robot automatically navigates between the starting point and the target point, it bypasses obstacles; and if necessary, sets a new path of the route to reach the goal point.Â Â